Künstler des Jahrhunderts. (Köln : Baukunst-Galerie, 1991)
Organ, Brian ; Dix, Otto ; Sigg, Hermann A. ; Moore, Henry ; Seigle, Henri ; Paetz, Eric ; Jenkins, Paul ; Muzika, Frantisek ; Ernst, Max ; Wunderlich, Paul ; Tobey, Mark ; Ackermann, Max ; Ritschl, Otto ; Schürz, Curt ; Henkel, Manfred ; Schultze, Bernard ; Santana, Nestor ; Anderle, Jiri ; Keilitz, Dietmar ; Uzzell, Glyn ; Liu Guo-Hui ; Akai, Fujio ; Kolbe, Georg ; Krause, Karl-Heinz ; Haase, Volkmar ; Martin, Roland ; Jecza, Petru
Künstler des Jahrhunderts, Baukunst-Galerie, Köln, 5. Juni 1991
boek